Correlation between the levels of urea serum, creatinine, and haemoglobin with fatigue in patient with Chronic Kidney Disease at Haemodialisa Unit, dr. R. Goeteng Taroenadibrata General Hospital Purbalingga - Sufia Arhamawati; Saryono Saryono; Sidik Awaluddin (Journal of Bionursing, 2019)
Background : Chronic kidney disease is a progressive destruction of renal structure and continuously. Fatigue is one of the few complaints that often felt by patients with chronic kidney disease. Prevalence of fatigue in patients with chronic kidney disease is high. Patients with chronic kidney disease characterized by elevated levels of serum urea, creatinine, and decreased levels of haemoglobin.Objective : To determine correlation between the levels of serum urea, creatinine, and haemoglobin with fatigue in patients with chronic kidney disease at Haemodialisa Unit, dr. R. Goeteng Taroenadibrata General Hospital Purbalingga.Method : This research using observational analytic design with cross sectional study conducted in dr. R. Goeteng Taroenadibrata General Hospital Purbalingga. The samples used were 30 patients with total sampling technique. The research instrument used secondary data from laboratory test result and questioner with interview.Result : Characteristics of respondents for the ages at most between 50-57 years that was 33,00%. For gender, male sex more than female, male 17 respondents female 13 respondents. And private sector workers had the highest number with 11 respondents (36,67% ). Mean of the serum urea levels as much as 158,09; creatinine levels 12,00; haemoglobin levels 8,19; and the fatigue’s score 29,90. The result of this study, there was no correlation between the serum urea levels with fatigue (p = 0,928 ; ? = 0,05), there was no correlation between creatinine with fatigue ( p = 0,863 ; ? = 0,05 ), and there was significant correlation between haemoglobin with fatigue with negative moderate correlation between the variables (p = 0,021 ; ? = 0,05; r = -0,419).Conclusion : The lower haemoglobin levels the increase fatigue scores.